Rationalizing the Decavanadate(V) and Oxidovanadium(IV) Binding to G-Actin and the Competition with Decaniobate(V) and ATP - Sciortino, Giuseppe (Inorg Chem, 2020)
[Image: see text] The experimental data collected over the past 15 years on the interaction of decavanadate(V) (V(10)O(28)(6–); V(10)), a polyoxometalate (POM) with promising anticancer and antibacterial action, with G-actin, were rationalized by using several computational approaches (docking, density functional theory (DFT), and molecular dynamics (MD)). Moreover, a comparison with the isostructural and more stable decaniobate(V) (Nb(10)O(28)(6–); Nb(10)) was carried out. Four binding sites were identified, named α, β, γ, and δ, the site α being the catalytic nucleotide site located in the cleft of the enzyme at the interface of the subdomains II and IV. It was observed that the site α is preferred by V(10), whereas Nb(10) is more stable at the site β; this indicates that, differently from other proteins, G-actin could contemporaneously bind the two POMs, whose action would be synergistic. Both decavanadate and decaniobate induce conformational rearrangements in G-actin, larger for V(10) than Nb(10). Moreover, the binding mode of oxidovanadium(IV) ion, V(IV)O(2+), formed upon the reduction of decavanadate(V) by the –SH groups of accessible cysteine residues, is also found in the catalytic site α with (His161, Asp154) coordination; this adduct overlaps significantly with the region where ATP is bound, accounting for the competition between V(10) and its reduction product V(IV)O(2+) with ATP, as previously observed by EPR spectroscopy. Finally, the competition with ATP was rationalized: since decavanadate prefers the nucleotide site α, Ca(2+)-ATP displaces V(10) from this site, while the competition is less important for Nb(10) because this POM shows a higher affinity for β than for site α. A relevant consequence of this paper is that other metallodrug–protein systems, in the absence or presence of eventual inhibitors and/or competition with molecules of the organism, could be studied with the same approach, suggesting important elements for an explanation of the biological data and a rational drug design.